Metformin – an old drug with a new face - Galicka-Latała, Danuta; Małecki, Maciej T. (Przewodnik Lekarza/Guide for GPs, 2007)
One of the most difficult current medical problems is the growing epidemic of type 2 diabetes mellitus. This disease results in dangerous chronic complications and increased mortality, mainly due to cardiovascular causes. Two major pathophysiological mechanisms underlying the occurrence of type 2 diabetes are impaired insulin secretion and decreased insulin sensitivity. Metformin is the most popular drug enhancing sensitivity to insulin. Over the last decade it has been the subject of scientific and clinical studies that clarified its role in the field of diabetology. This review summarizes the role of metformin in type 2 diabetes therapy.